2015
DOI: 10.1038/jcbfm.2014.209
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Ethanol Increases Dopamine Release in the Ventral Striatum in Humans: PET Study Using Bolus-Plus-Infusion Administration of [11C]raclopride

Abstract: Ethanol increases the interstitial dopamine (DA) concentration in the nucleus accumbens (NAcc) of experimental animals, but positron emission tomography (PET) studies using the single-bolus protocol of the [ 11 C]-raclopride competition paradigm have yielded conflicting results in humans. To resolve disparate previous findings, we utilized the bolus-plus-infusion (B/I) method, allowing both baseline and intervention quantification of [ 11 C]raclopride binding during a single 105-minute PET scan, to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…At the level of the striatum, we found a nonstatistically significant decrease of −6.6% in binding within the LST under the alcohol condition compared to the placebo condition (Cohen's d = 0.64). Previous [ 11 C]‐raclopride studies have similarly demonstrated decreased binding in the ventral striatum (the anatomical correlate of the LST) at magnitudes of 6 to 15% (Aalto et al., ; Boileau et al., ; Oberlin et al., ; Ramchandani et al., ; Setiawan et al., ; Urban et al., ). Importantly, the moderate effect of alcohol on the LST in the present study is congruent with other oral administration [ 11 C]‐raclopride studies using similar samples heterogeneous in sex, drinking history, and family history of alcoholism (Setiawan et al., ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…At the level of the striatum, we found a nonstatistically significant decrease of −6.6% in binding within the LST under the alcohol condition compared to the placebo condition (Cohen's d = 0.64). Previous [ 11 C]‐raclopride studies have similarly demonstrated decreased binding in the ventral striatum (the anatomical correlate of the LST) at magnitudes of 6 to 15% (Aalto et al., ; Boileau et al., ; Oberlin et al., ; Ramchandani et al., ; Setiawan et al., ; Urban et al., ). Importantly, the moderate effect of alcohol on the LST in the present study is congruent with other oral administration [ 11 C]‐raclopride studies using similar samples heterogeneous in sex, drinking history, and family history of alcoholism (Setiawan et al., ).…”
Section: Discussionmentioning
confidence: 91%
“…The acute dopaminergic response to alcohol has also been studied in humans through positron emission tomography (PET), but the results are largely inconsistent. Decreased radiotracer binding in the ventral striatum, indicative of increased DA release, has been demonstrated following either oral or intravenous alcohol in some studies of nondependent drinkers (Aalto et al., ; Boileau et al., ; Urban et al., ; Yoder et al., ) but not in others (Salonen et al., ; Yoder et al., , , ). Still, other investigations have evidenced an increase in DA only in subsets of healthy drinkers possessing specific personality and genetic phenotypes (Ramchandani et al., ; Setiawan et al., ).…”
mentioning
confidence: 98%
“…There was no apparent effect on IV alcohol on VST DA in the Ramchandani et al 118AA sample, which is consistent with data in the present study. Aalto et al (2015) reported alcohol-induced DA release in 9 social drinkers using a bolus-infusion RAC PET protocol. The bolus-infusion approach, as in our design, measures baseline and challenge conditions successively within the same session, and thus avoids between-day variance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there were no apparent effects in subjects homozygous for the major 118A allele. More recently, Aalto et al reported striatal DA release from a bolus IV alcohol infusion in a small group of social drinkers (Aalto et al, 2015), although imaging during this non-PBPK paradigm may have captured both ascending and descending limbs of brain alcohol exposure. Taken together, the PBPK-IV clamp data seem to suggest that IV alcohol may not produce a robust DA response in social drinkers; however, Type II error cannot be ruled out, given the sample sizes of all three PBPK-based infusion studies.…”
Section: Introductionmentioning
confidence: 99%
“…As noted earlier, the mesolimbic reward circuit features prominently in most theories of addiction, and this has stimulated many human imaging studies that have characterized the acute and chronic alcohol effects on VTA–NAc DA signaling. Several studies have employed PET imaging to explore the effects of alcohol consumption on ventral striatal DA levels in healthy subjects, and most (Aalto et al ; Boileau et al ; Oberlin et al ; Urban et al ), but not all (Salonen et al ), reported significant increases in DA levels in this brain region. Several recent studies used a dynamic intravenous alcohol clamp procedure to control for chemo‐ and somatosensory alcohol cues that may affect mesolimbic DA signaling.…”
Section: Anatomy and Circuitry Of Comorbid Ptsd And Audmentioning
confidence: 99%